Analisis Penerapan Biaya Operasional Penggunaan Pupuk NPK Tanaman Kelapa Sawit Kebung Bengabing PT Fajar Agung pada Masa Pandemi Tahun 2022 - Ela Sapitri; Nurlaila Nurlaila (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This research was carried out by the author so that the PT. Fajar Agung Office coukd carry out operational activities ad maximiza the awareness and safety aspects of work carried out by office employyes in order to create work comfort and optimal performance of their employees. If employess who work feel comfortable and satisfied, their performance will have a postitive impact and are believed to be able to provide benefits for the office. Appropriate operational activities and maximizing the awareness and safety aspects of work carried out by office employees in order to create work comfort and optimal performance of their employees, both during norma times and during the COVID 19 pandemic. Operational cost are a very important part of company. These operational costs very helpful on any costs incurred and also on the efficiency stock management. Operational costs only focus on the costs and needs nedeed from a company and measure the income earned from company . This research was conducted using descriptive qualitative methods by taking primary data from direct companies. From the research, it can be sseen regarding the importance of reporting operational costs in a company, namely to organize all forms of income and expenditure activities required by the company. Operational costs are costs that have an important influence on achieving the goals or targets of the company. In addition, operational cost have a goal so that all types of costs carried out becaome more focused and report regularly.